STUDI KRITIS PERNIKAHAN BAWAH UMUR PERSPEKTIF UUP NO. 16 TAHUN 2019 DAN GENDER ANALISIS - Sippah Chotban (Al-Risalah, 2020)
The age of marriage between women and men in the legal structure in Indonesia is an important element and becomes a tough polemic and discourse among academics, practitioners and political elites. This is indicated by, among other things, the following discourse and regulations that specifically regulate marital age, namely Marriage Law Number 1 of 1974 Article 7 (1) which confirms that the marriage age limit is 16 for women and 19 for men. The marriage age limit provisions are further reaffirmed in Article 15 (1) of the Compilation of Islamic Law (KHI) No. 1 of 1991. In its development, the marriage age limit has not fulfilled a sense of justice, until legal measures are taken to review it, so UUP No. 16 of 2019 Article 7 paragraph 1 which states that the age limit for marriage of women and men is 19 years. Equal age restrictions have a purpose - among other things - to create early equality between women and men in marriage, while at the same time being able to suppress and minimize underage marriages so that marital human rights can be realized, as well as destructive things -negative does not happen. The problem then is whether the presence or presence of UUP No. 16 of 2019 will reduce and minimize the number of underage marriages? And will this create an atmosphere of domestic life that is far from manifestations of gender inequality?